The Spanish translation of the cultural element妾 (Qiè) in the Chinese novel Hong Lou Meng - Duoyuan, Hu (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this world, no two cultures are the same; translation is an intercultural communication activity. In the 1990s, Suan Bussnett proposes “the culture turn”, and emphasizes that translation should not be isolated from culture. As an important culture 妾 (Qiè) is filled in the novel Hong Lou Meng. From the perspective of “culture translation”, puts focus on how the meaning can be translated, also conveying the cultural information of 妾 (Qiè).